2022
DOI: 10.3390/healthcare10071319
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Equity and Influencing Factors of Medical and Health Resources Allocation in the Context of COVID-19: A Case of Taiyuan, China

Abstract: COVID-19 has killed millions of people worldwide. As a result, medical and health resources continue to be strained, posing a great threat to people’s safety and economic and social development. This paper built the index system of influencing factors of medical and health resources containing the economy, population and society, and then classified Taiyuan into three types of regions by cluster analysis. The Gini coefficient, Theil index and agglomeration degree were then used to analyze the spatial distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…The grey correlations showed that population structure factors has a greatest impact on the regional inequality of emergency medicine department beds, which is consistent with the findings of Wu et al [ 5 ]. Children and the elderly population, who are physically weaker due to age, tend to be at higher risk of acute illness and injury, and have a greater need for emergency care.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The grey correlations showed that population structure factors has a greatest impact on the regional inequality of emergency medicine department beds, which is consistent with the findings of Wu et al [ 5 ]. Children and the elderly population, who are physically weaker due to age, tend to be at higher risk of acute illness and injury, and have a greater need for emergency care.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, the distribution of resources shows more equal in terms of population, while inequality still exists among regions. Medical institutions, medical staff and beds, and other medical resources were distributed unequally by geographical with Gini coefficients exceeding 0.7 [ 5 ]. This leads to a large number of people living within the county having not enough resources for emergency care and poor access to healthcare [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the pandemic the causes of mortality have changed compared to the previous 5 years, creating a scenario of causality that is difficult to interpret [ 35 , 51 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, there was careful planning and management of resources in preparation for the surge of potential patients with the highest acuity. It was, therefore, possible to avoid ED crowding, even during extreme conditions, by leveraging previously known input, throughput and output factors, including a change in working methods with higher competence, less diagnostics, and increased focus on rapid clinical admission decisions [ 14 , 27 ].…”
Section: Discussionmentioning
confidence: 99%